Kelapa Sawit dan Bencana Alam: Makna Sosiologis Diskursus Dampak Ekologis Ekspansi Sawit - Siska Adhariani; Afrizal Afrizal (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2021)
Since its inception and until now, oil palm plantations have been controversial in Indonesia. Although there is ample evidence presented by proponents proving that oil palm expansion has made an important contribution to the Indonesian economy, from an ecological point of view, it is claimed by critics to have negative impacts on the environment, one of which is the cause of natural disasters. The link between oil palm expansion and natural disasters is debated between critics and supporters of oil palm expansion. This study examines the theme of criticism of oil palm expansion as a cause of natural disasters and counter-discourse of supporting oil palm expansion. By using literature study methods and an environmental, sociological perspective, it is found that the discourse on the impact of oil palm plantation expansion shows a contradiction between the views of the New Ecological Paradigm (Paradigma Ekologi Baru or PEB) and the Human Exemptionalism Paradigm (Paradigma Keterpisahan Manusia or HEP). The Indonesian government is building a counter-discourse of ecological modernization to maintain and develop oil palm plantations expansion.